Makna Teologis Keturunan sebagai Pemberian Allah bagi Keluarga dalam Perjanjian Lama - Yohanes K. Susanta (P3TK, Sanata Dharma University, 2017)
Barrenness is a serious problem for couples in a culture that emphasizes the importance of generating descendants such as one of the time of the Judeo-Christian Scripture. This writing offers a theological reflection that comes from the Old Testament. Children is Gods grace for the family. Nevertheless, having no children should no longer be seen solely as a burden for a couple but rather as part of the mystery of God's grace for their lives as family. God may use barrenness to increase faith in God. God may direct barren married couple to use their time and freedom to serve Him. Still, God may use barrenness as an opportunity for adoption. Finally, God may use barrenness as a witness to those who have children to cherish them as God's grace.